(untitled) (Eureka Journal of Computing Science & Digital Innovation, 2026)
This article examines the use of digital tools and online platforms in teaching computer skills to students of technical colleges in Uzbekistan. The study emphasizes the importance of integrating interactive technologies into vocational education to enhance practical learning and professional competence. Various approaches, including virtual labs, simulation software, multimedia resources, and online learning platforms, are analyzed for their effectiveness in developing students’ technical skills, problem-solving abilities, and independent learning. The article highlights how digital tools increase student engagement, motivation, and participation while allowing personalized and flexible learning. The findings suggest that combining traditional teaching methods with modern technological resources creates a more effective, interactive, and learner-centered environment, better preparing students for real-world technical and professional challenges.